Restatement of Contemporary Sufi Epistemology: The Case of Badiuzzaman Said Nursi - rodi, Agisni; Ihsan, Nur Hadi; Hidayat, Muhammad Sofian (Islam Transformatif : Journal of Islamic Studies, 2023)
This study aims to explore the epistemological construct of Sufism according to Said Nursi in the contemporary era. Sufism is seen as having deviant concepts and practices contrary to Sharia in the modern era. Some muslim and non-muslim thinkers argue that Sufism does not originate from Islam. Therefore, there needs to be an effort to decipher this misunderstanding by exposing how Sufism's epistemology was genuinely constructed by referring to the teachings and practices of a contemporary Sufi, Sa'id Nursi. This study is qualitative library research. Data in this study, both primary and secondary, were collected using documentary techniques. The collected data were analyzed utilizing the content analysis method. This work finds that Nursi outlines four pillars of Sufism epistemology. First, true Sufism is based on the Qur'an and Sunnah, internalized and manifested through the soul and heart, as is the view of the authoritative Sufis. Second, purification of the teachings and practices of Sufism must depart from the purgation of the heart and soul. Third, social equality refers to carrying out lifes values, meaning that all are equal before Allah SWT. Fourth, consistently instill the Qurans four values: tauhid (unity and oneness of God), nubuwah (prophecy), hashr (resurrection), and 'adl (justice).